The Effects of Paid Family Leave in California on Labor Market Outcomes - Charles L. Baum; Christopher J. Ruhm (Institute for the Study of Labor (IZA), 2014)
Using data from the 1997 cohort of the National Longitudinal Survey of Youth (NLSY-97), we examine the effects of California's paid family leave program (CA-PFL) on mothers' and fathers' use of leave during the period surrounding child birth, and on the timing of mothers' return to work, the probability of eventually returning to pre-childbirth jobs, and subsequent labor market outcomes. Our results show that CA-PFL raised leave-taking by around three weeks for the average mother and approximately one week for the average father. The timing of the increased leave use immediately after birth for men and around the time that temporary disability insurance benefits are exhausted for women is consistent with causal effects of CA-PFL. Rights to paid leave are also associated with higher work and employment probabilities for mothers nine to twelve months after birth, possibly because they increase job continuity among those with relatively weak labor force attachments. We also find positive effects of California's program on hours and weeks of work during their child's second year of life and possibly also on wages.
Keywords: J1; J2; J3; J13; J18; 330; parental leave; paid leave; family leave; employment; wages; leave-taking; return-to-work decisions